Effect of serum source on in vitro maturation and fertilizationof pre pubertal goat oocytes - YADAV, E N; KHARCHE, S D; GOEL, A K; JINDAL, S K; SINHA, N K; JOHRI, D K (The Indian Journal of Animal Sciences, 2011)
Oocyes were recovered from pre-pubertal goat ovaries of abattoir origin using puncture technique; washed in TCM199 containing gentamicin (50 Jlg/ml) and divided into 4 groups. Group 1 oocytes (160) were matured in a medium rCM ... 199 supplemented with 20% estrous goat serum (EGS); group 2 oocytes (194) were matured in a medium TeM - 199 supplemented with 20% estrous sheep serum (ESS); group 3 oocytes (154) were matured in a medium TCM- 199 supplemented with 20% fetal bovine serum (FBS); and group 4 oocytes (123)were matured in a medium TCM-199 without serum supplementation as a control. After 27h culture, 80.70 and 83.12 %maturation rates were obtained based on cumulus cell expansion in EGS, ESS and PBS, respectively. Anonsignificant difference was observed between EGS and FBS but both differed significantly with ESS. Conversely a very low maturation rate (8.94%) was observed in the medium lacking serum (control). Oocytes were separated from cumulus cells by treating with 0.1% hyaluronidase, passed through a fine pipette and co-cultured with capacitated spermatozoa with final concentration 1xl06 spennJrnl in Fert TALP medium. After 18h of CO-CUlture, oocytes were separated from adhered spenn cells and transferred in embryo development medium (EDM). At 48h post insemination cleavage rates was observed as 70.89, 38.69, 72.66 and 36.36% in oocytes matured in different maturation media supplemented with EGS, ESS, and control, respectively. Asignificant difference was observed between EGS and ESS, FBS and ESS supplementation. In conclusion the EGS and PBS sera can be substituted from one and other for in vitro maturation of prepubertal goat oocytes. However EGS is superior to PBS with respect to cost economy, therefore, EGS can be used routinely for the IVM and IVF of pre-pubertal goat oocytes.Â